2015
DOI: 10.1038/ncomms8401
|View full text |Cite
|
Sign up to set email alerts
|

Kumada–Grignard-type biaryl couplings on water

Abstract: Well-established, traditional Kumada cross-couplings involve preformed Grignard reagents in dry ethereal solvent that typically react, e.g., with aryl halides via Pd catalysis to afford products of net substitution. Therefore, in the work described, which appears to be counterintuitive, exposure of these same aromatic halides to catalytic amounts of Pd(II) and excess magnesium metal in pure water leads to symmetrical/unsymmetrical biaryls, indicative of a net Kumada-like biaryl coupling. Evidence is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In the first step, Ag I is oxidized to an Ag II species, and the continuity of the redox reactions led to the formation of phenylmethanimine (5), and again the combination of redox and hydrolysis reac-tion led to the formation of benzamide (10) and benzaldehyde (6). The formation of benzaldehyde, benzamide, and benzoic acid (7) was unequivocally detected during GC measurements, and can also be seen in the reaction time-profile in the earlier stages of the reaction (Figure 2). A control reaction again confirmed that benzaldehyde, benzamide and benzoic acid were formed during the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step, Ag I is oxidized to an Ag II species, and the continuity of the redox reactions led to the formation of phenylmethanimine (5), and again the combination of redox and hydrolysis reac-tion led to the formation of benzamide (10) and benzaldehyde (6). The formation of benzaldehyde, benzamide, and benzoic acid (7) was unequivocally detected during GC measurements, and can also be seen in the reaction time-profile in the earlier stages of the reaction (Figure 2). A control reaction again confirmed that benzaldehyde, benzamide and benzoic acid were formed during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Next, self-condensation of benzaldehyde and BzA gave N-benzylidene-1-phenylmethanamine (8). In the next step, the redox reaction led to the formation of N-benzylbenzamide (9, detected by GC analysis) and again consecutive redox processes generated benzoic acid (7). The ensuing redox reaction oxidizes the benzoic acid (7), leading to decarboxylation and aryl radical generation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Fe‐catalyzed Csp 2 –Csp 3 Kumada coupling of chlorobenzamides have been reported at 0 °C . An interesting article for the biaryl synthesis by homo‐ and hetero‐Kumada couplings in water has also been reported . Feringa and co‐workers have reported the use of Pd‐phosphine catalysts for the coupling of organolithium reagents and found that, despite high turnover frequencies, coupling below −10 °C was not feasible …”
Section: Methodsmentioning
confidence: 99%
“…Using the molecular formula as evidence, a simple symmetric biaryl system was deduced as 2,2',4,4'-tetramethoxybiphenyl (3). Although this compound has been obtained by synthesis, 18 to the best of our knowledge, it is the first description of 3 as a natural product. A similar structure was proposed in a PhD thesis but NMR data were not fully consistent.…”
Section: Figure 1 Structures Of the New Metabolites Isolated From Lmentioning
confidence: 99%